Invasive Salmonella infections among children in Bintulu, Sarawak, Malaysian Borneo a 6-year retrospective review - Mohan, Anand; Munusamy, Chandran; Tan, Yee Chin; Muthuvelu, Sobana; Hashim, Rohaidah; Chien, Su Lin; Wong, Ming Kui; Nurul Aiman, Khairuddin; Yuwana, Podin; Lau, Peter Sie Teck; Ng, David Chun Ern; Ooi, Mong How (MC Infectious Diseases, 2019)
Background: Invasive Salmonella infections result in significant morbidity and mortality in developing countries. In Asia, typhoid and paratyphoid fever are reported to be the major invasive Salmonella infections, while invasive nontyphoidal Salmonella (iNTS) infections are believed to be uncommon. Data from Sarawak, in Malaysian Borneo, are limited. Methods: A retrospective study identifying all children aged < 15 years with invasive Salmonella infections from 2011 to 2016 was conducted in Bintulu Hospital in Sarawak. Population incidences, clinical and bacterial characteristics were examined. Results: Forty-four patients were identified during the 6-year study period: 43 had iNTS infection and 1 had typhoid fever. The average annual iNTS incidence was 32.4 per 100,000 children aged < 5 years. None of the children had malaria or HIV infection, and only 7% were severely malnourished. Salmonella Enteritidis and Salmonella Java were the commonest NTS serovars identified. Pneumonia was the most common manifestation of iNTS disease, present in 20 (47%) children. Other manifestations included gastroenteritis, fever without a source, septic arthritis and meningitis. Salmonella Enteritidis was identified in 76% of those with pneumonia, significantly more frequently than in children with other manifestations. Over 25% of children with iNTS developed severe disease and nearly 10% suffered long term morbidity or mortality. While 78% of Salmonella Java isolates were multidrug resistant, nearly all other isolates were susceptible to most antimicrobials, including ampicillin. Conclusions: Bintulu Division in Sarawak observed a very high incidence of childhood iNTS infections. Enteric fever was uncommon. The epidemiology of invasive Salmonella infections in Malaysian Borneo differs considerably from that of neighbouring countries in Asia. Keywords: Salmonella, Invasive, Non-typhoidal, Children, Malaysia, Borneo